Tata Kelola Good Corporate Governance Pada PT. Bank Muamalat KC Medan Balaikota Tahun 2022 - Iqbal, M.; Daulay, Adelia Natasya; Nugroho, Dimas Akbar; Lubis, Jainuar Amarullah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to analyze the implementation of Good Corporate Governance at PT. Bank Muamalat KC Medan City Hall. This research aims to understand the phenomena experienced by research subjects, and by means of descriptions in the form of words and language in a special natural context and by utilizing various scientific methods, descriptive research is research that is intended to find out information about the status of symptoms. existing, namely the state of symptoms according to what they were at the time the research was carried out. The results of the research explain that the activities at Bank Muamalat KC Medan Balaikota are in accordance with the sharia principles of Good Corporate Governance. The application of Good Corporate Governance principles has also been implemented well in the field. Even though implementing the principles of Good Corporate Governance sometimes there are still obstacles, they can still be overcome in a professional manner and to maintain development and maintain the quality and progress of Bank Muamalat KC Medan Balaikota.